Orientalizing the Jew : religion, culture, and imperialism in nineteenth-century France - Kalman, Julie, 1969- (Modern Jewish experience (Bloomington, Ind.), 2017)
Orientalizing the Jew shows how French travelers depicted Jews in the Orient and then brought these ideas home to orientalize Jews living in their homeland during the 19th century. Julie Kalman draws on narratives, personal and diplomatic correspondence, novels, and plays to show how the "Jews of the East" featured prominently in the minds of the French and how they challenged ideas of the familiar and the exotic. Portraits of the Jewish community in Jerusalem, romanticized Jewish artists, and the wealthy Sephardi families of Algiers come to life. These accounts incite a necessary conversation about Jewish history, the history of anti-Jewish discourses, French history, and theories of Orientalism in order to broaden understandings about Jews of the day.